2015
DOI: 10.1111/pan.12827
|View full text |Cite
|
Sign up to set email alerts
|

Validity of sidestream endtidal carbon dioxide measurement in critically ill, mechanically ventilated children

Abstract: Sidestream capnography in mechanically ventilated infants and children seems moderately reliable and valid when corrected for individual differences. Therefore, it could only be used with caution for trend estimation in the individual patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
3
1
Order By: Relevance
“…Similar to Mehta et al, McDonald et al 13 demonstrated that increased lung disease had a negative effect on the PETCO 2 correlation with PaCO 2 . In contrast with previous studies, van der Heijden et al 17 reported that factors indicating severe lung disease did not adversely affect the relationship between ETCO 2 and PaCO 2 . However, they stated that this may be due to the high respiratory morbidity in their sample, resulting in relatively little variance in these parameters.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Similar to Mehta et al, McDonald et al 13 demonstrated that increased lung disease had a negative effect on the PETCO 2 correlation with PaCO 2 . In contrast with previous studies, van der Heijden et al 17 reported that factors indicating severe lung disease did not adversely affect the relationship between ETCO 2 and PaCO 2 . However, they stated that this may be due to the high respiratory morbidity in their sample, resulting in relatively little variance in these parameters.…”
Section: Discussioncontrasting
confidence: 69%
“…4,6,13,16 In a study that examined the correlation between 341 PaCO 2 and ETCO 2 measurements of 47 patients who received MV, sidestream capnography in mechanically ventilated infants and children appeared to have moderate reliability and validity when corrected for individual differences. 17 Results of another study using sidestream capnography indicated that ETCO 2 gave an excellent value of the PaCO 2 in children older than 8 months. 18 Though mainstream capnography was used in our study, a significant correlation was found between the limited number of PaCO 2 and ETCO 2 , in accordance with the two aforementioned studies.…”
Section: Discussionmentioning
confidence: 96%
“…Both main- and side- stream capnographs are placed in-line with the ventilator circuit, between the ETT and ventilator tubing ( 10 ). The difference between them is where the CO 2 is analysed.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical real-time interpretation of waveforms may identify life threatening complications of mechanical ventilation such as dislodged or blocked ETT (7), or describe established or impending lung pathologies (8). The CO 2 waveforms are more useful when evaluated with the concurrent flow, volume and pressure waveforms (9), although not all ventilators present them at a synchronous scale. This short overview aims to cover the practical basics of neonatal capnography, providing an for clinicians asking the following question: "In newborn infants requiring mechanical ventilation, what value does the capnography waveform have in supporting diagnosis and clinical troubleshooting?…”
Section: Introductionmentioning
confidence: 99%